2016
DOI: 10.1021/acs.chemrev.6b00284
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Carbon and Sulfur Tolerant Solid Oxide Fuel Cell Materials, Incorporating Lessons from Heterogeneous Catalysis

Abstract: Solid oxide fuel cells (SOFCs) are a rapidly emerging energy technology for a low carbon world, providing high efficiency, potential to use carbonaceous fuels, and compatibility with carbon capture and storage. However, current state-of-the-art materials have low tolerance to sulfur, a common contaminant of many fuels, and are vulnerable to deactivation due to carbon deposition when using carbon-containing compounds. In this review, we first study the theoretical basis behind carbon and sulfur poisoning, befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
178
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(182 citation statements)
references
References 471 publications
(1,130 reference statements)
4
178
0
Order By: Relevance
“…To date, extensive studies have shown that Ni is the preferred electrocatalyst for fuel electro‐oxidation in SOFCs due to its superior activity, conductivity, and thermal compatibility 15, 16. However, this catalyst must be modified to enable its direct use with fossil fuels.…”
mentioning
confidence: 99%
“…To date, extensive studies have shown that Ni is the preferred electrocatalyst for fuel electro‐oxidation in SOFCs due to its superior activity, conductivity, and thermal compatibility 15, 16. However, this catalyst must be modified to enable its direct use with fossil fuels.…”
mentioning
confidence: 99%
“…Since a high temperature is required for methane reforming (>800°C), Boudouard reaction would not be significant . Therefore, the dissociation of methane, which may occur via four steps (CH 4 →*CH 3 →*CH 2 →*CH), constitutes the main contribution to carbon deposition in DRM . Carbon formation by CH 4 decomposition is a structure‐sensitive reaction .…”
Section: Dry Reforming Of Methanementioning
confidence: 99%
“…Therefore, the dissociation of methane, which may occur via four steps (CH 4 →*CH 3 →*CH 2 →*CH), constitutes the main contribution to carbon deposition in DRM . Carbon formation by CH 4 decomposition is a structure‐sensitive reaction . For example, the Ni (100) and Ni (110) surfaces are more active for the decomposition of CH 4 to carbon than the Ni (111) surface.…”
Section: Dry Reforming Of Methanementioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the reaction pathway and the form of deposited carbon, deactivation of the catalyst may occur due to blockage of macro-and micro-gas diffusion channels, growth of carbon-whiskers, strong chemisorption of carbon-monolayers or complete encapsulation of the metal particles (1). Generally, this causes rapid and irreversible degradation of the cell.…”
Section: Introductionmentioning
confidence: 99%